GROWTH AND POPULATION DYNAMICS OF THREE PENAEID PRAWNS IN THE TRAWLING GROUNDS OFF KAKINADA - Devi, S Lalitha (Indian Journal of Fisheries, 2011)
The von Bertalanffy growth parameters L „ , K and tn in P. monodon are estimated to be 357 mm, 1.206 and 0.041, respectively, in females and 296.9 mm, 2.316 and 0.138, respectively, in males. The Instantaneous rates of mortality Z, M and F are 5.13, 2.02 and 3.If in females and 10.58, 2.89 and 7.69 in males. There is thus scope to increase the yield of the species by increasing effort. In M. monoceros the values were LB 216.2 mm, K = 0.996 and tc = —0.044 in females and L^ = 208.4 mm, K = 0.972 and t0 = —0.063 in males. The Instantaneous rates of mortality values are Z = 5.49, M = 1.84 and F = 3.65 in females and Z = 7.98, M = 1.81 and F = 6.17 in males, showing that this species also is capable of increasing the yield.